(untitled) (Revista Electrónica REDINE, 2024)
The intention of this essay focuses on reflecting on teaching practice from the perspective of being a teacher as a professional who generates and transforms knowledge in its context. We interpret the curriculum, from epistemic thinking, as a flexible, recursive, and unfinished framework, which allows interaction and interdependence between the different elements of the curriculum intertwined to provide a meaningful educational experience in an evolving society. We understand that the teacher as an epistemic subject, in curricular construction, should develop the following functions: (a) Researcher, of socio-educational phenomena, (b) Curriculum builder, to design innovative proposals, (c) Change agent, by promoting development social from a scientific and technological perspective. Finally, the transformative potential of education to cultivate human and social development, with the teacher as a key agent in this process. It is part of the research line Curriculum Innovations in and for Social Development of the UPEL-IPB.